Stability of interceptive/corrective orthodontic treatment for tooth ankylosis and Class II mandibular deficiency: A case report with 10 years follow-up - Carlos Henrique Guimarães; José Fernando Castanha Henriques; Guilherme Janson; Wilana S Moura (Wolters Kluwer Medknow Publications, 2015)
The purpose of this article is to present the treatment of a 8-year-old boy with tooth ankylosis in teeth 85 and Class II division 1 malocclusion and to report a 10-year follow-up result. The patient was initially treated with a sagittal removable appliance, followed by an eruption guidance appliance and braces. The interceptive orthodontic treatment performed to recover the space lost by ankylosis of a deciduous tooth allowed a spontaneous eruption and prevented progression of the problem. The use of an eruption-guidance appliance corrected the dentoskeletal Class II, thus improving the patient's appearance. Besides the treatment producing a good occlusal relationship with the Class I molar, the correction of the overjet and overbite was stable over a ten-year period.